Safety of hematopoietic cell infusion in children with malignant and non‐malignant diseases. (28th August 2017) - Heneghan, Chelsea; Smilow, Elana; Tanhehco, Yvette; Jin, Zhezhen; Cofnas, Paige; Schwartz, Sharon; Patel, Nita; Carberry, Deborah; Silverman, Justin; Huynh, Paul; Hagan, Brittany; Tobin, Kim; et al.
Abstract: HPC infusions have been associated with a variety of adverse events related to either patient or HPC product‐related factors. Studies documenting infusion‐related AEs in children are limited. We reviewed HPC infusion records in 354 children. Infusion‐related adverse events were classified as follows: grade 0—absent, grade I—mild, grade II—moderate, grade III—severe, grade IV—life‐threatening, and grade V—death. The percentage of patients with grade 0, I, and II‐IV AEs was as follows: 0 = 67%, I = 23.4%, and II‐V = 9.6% (one patient had fatal anaphylactic reaction to dimethyl sulfoxide). The incidence of grade II‐IV hypertension was 7.1%. There was a higher incidence of AEs with infusion of allogeneic bone marrow versus allogeneic PBSCs (47.4% vs 25.3%, P  = .001). Cryopreserved products had a lower incidence of infusion‐associated AEs compared with fresh HPC products (24% vs 39.4%, P  = .003). Allogeneic HPC infusion volume (>100 mL) was a significant risk factor for infusion‐associated AEs ( P  < .001). Patients >10 years who received autologous HPC infusions had higher risk of AEs when compared to patients <10 years ( P  = .01). Our study demonstrated that despite a high incidence of infusion‐associated hypertension, HPC infusion is relatively safe in children. Investigating strategies to optimize management of hypertension in the setting of HPC infusion is warranted.